STABILITAS DAN DEFORMASI PADA TANAH LEMPUNG LUNAK DI BENDUNGAN TERITIP - Rasita Mulyati; Goji Pamungkas (Rang Teknik Journal, 2022)
Dams on soft soils differ greatly in behavior when compared to rock foundations. Potential dam failures can occur due to differential settlement. The total reduction in Barnacle dam without PVD takes 17 years. Analysis of the use of PVD shows an increase in shear strength due to dissipation of pore stresses marked by an increase in safety figures. The time needed to achieve consolidation of at least 80% is 180 days based on finite element simulations. The total reduction in the body of the dam is 1.37 meters.